Micro‐ and Mesoporous Carbide‐Derived Carbon–Selenium Cathodes for High‐Performance Lithium Selenium Batteries. Issue 1 (8th August 2014) - Lee, Jung Tae; Kim, Hyea; Oschatz, Martin; Lee, Dong‐Chan; Wu, Feixiang; Lin, Huan‐Ting; Zdyrko, Bogdan; Cho, Won Il; Kaskel, Stefan; Yushin, Gleb
<x xml:space="preserve">Abstract</x> Nanocomposites of selenium (Se) and ordered mesoporous silicon carbide‐derived carbon (OM‐SiC‐CDC) are prepared for the first time and studied as cathodes for lithium‐selenium (Li‐Se) batteries. The higher concentration of Li salt in the electrolytes greatly improves Se utilization and cell cycle stability. Se‐CDC shows significantly better performance characteristics than Se‐activated carbon nanocomposites with similar physical properties. Se‐CDC also exhibits better rate performance and cycle stability compared to similarly produced sulfur (S)–CDC for Li/S batteries.